Scenario analysis for the future of audit in the European Union – strategic recommendations for Deloitte – scenario 2: people in control – narrative, strategy, and early indicators - Justino, Miguel Oliveira da Silva (2025)
This project examines the future of the audit industry in the European Union using the Intuitive-Logics School of scenario planning, centering around the intensive collaboration with experts from Deloitte. The aim is to address uncertainties, explore plausible future events, and develop effective strategies to navigate the evolving audit landscape. Based on the two key uncertainties, Level of talent availability and Extent of AI regulations, four different scenarios were developed. Moreover, the project provides specific strategic insights and offers actionable strategies to manage potential futures and improve Deloitte’s resilience in a rapidly changing environment.